Short Communication: Impact of introduction of managed honey bee colony on wild bee diversity and abundance in an agroecosystem in Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Widhiono I, Sudiana E, Suryaningsih S. 2022. Short Communication: Impact of introduction of managed honey bee colony on wild bee diversity and abundance in an agroecosystem in Indonesia. Biodiversitas 23: 1099-1104. Wild bees are natural pollinators of crops in agroecosystems, but managed honeybee colonies may diminish their diversity and abundance. We aimed to determine the impact of introducing managed honeybee (Apis cerana and A. mellifera) colonies on the diversity and abundance of wild bees in an agroecosystem in Indonesia. We introduced managed honeybee colonies into the plots containing four crops (tomato, green bean, chili, and green mustard). Sampling was conducted from March to July 2020 on the eastern slopes of Mount Slamet, Indonesia, at an elevation of 1241 m asl. Wild bee diversity was not affected by the introduction of managed honeybee colonies, but their abundance decreased at the end of the flowering period due to resource limitations. The most abundant wild bee species were Amegilla cyrtandrae and A. burneensis, and some wild bee species tended to be more abundant on certain crop species. We recommend that managed colonies be introduced during the early and mid-stages of crop flowering to reduce potential adverse effects on wild bee populations.
Keywords: Amegilla burneensis, Amegilla cyrtandrae, crops, Mount Slamet, phenology